Frontiers of Europe a transatlantic problem? - Bindi, Federiga M.; Angelescu, Irina (Brookings-SSPA series on public administration, 2011)
"Investigates the ramifications of enlarging the size of the European Union, including the effects on policies relating to energy, immigration, security, democracy and the rule of law, and economic development, and how a larger EU would affect NATO and relations with China, Latin America, Russia, and the United States"--Provided by publisher.